Inhibitory effects of methanolic Olea europaea and acetonic Acacia laeta on growth of Babesia and Theileria - Amany Magdy Beshbishy; Gaber El-Saber Batiha; Oluyomi Stephen Adeyemi; Naoaki Yokoyama; Ikuo Igarashi (Asian Pacific Journal of Tropical Medicine, 2019)
Objective: To evaluate the antipiroplasmic activities of methanolic extract of Olea europaea (MOE) and acetonic extract of Acacia laeta (AAL) against Babesia and Theileria parasites in vitro and evaluate the chemotherapeutic effects of these extracts against Babesia (B.) microti in vivo. Methods: Fluorescence assay using SYBR Green 1 nucleic acid stain was used to detect inhibitory effects of the two extracts as well as the combination effects of the two extracts with diminazene aceturate and atovaquone on four Babesia species and Theileria equi in vitro while for in vivo experiments, 8-weekold female BALB/c mice were injected intraperitoneally with 1 × 107B. microti-iRBCs and treated orally at a dose of 150 mg/kg of both extracts. Results: The half maximal inhibitory concentration (IC50) values of AAL against B. bovis, B. bigemina, B. divergens, B. caballi, and Theileria equi were lower than those of MOE extracts. Toxicity assay on Madin–Darby bovine kidney, mouse embryonic fibroblast (MH/3T3), and human foreskin fibroblast cell lines showed that MOE and AAL affected only the viability of Madin–Darby bovine kidney cell line with half maximal effective concentrations (EC50) of (794.7±41.9) and (873.9±17.5) μg/mL, respectively. The oral treatments of MOE and AAL at 150 mg/kg inhibited the growth of B. microti in mice by 80.4% and 64.4%, respectively. The MOE and diminazene aceturate combination showed a higher chemotherapeutic effect than that of monotherapy. Conclusions: MOE and AAL have the potential to be an alternative remedy for treating piroplasmosis. Furthermore, the combination therapy of MOE + DA was more potent against B. microti infection in mice than their monotherapies.